Activity-Stability Relationships in Oxide Electrocatalysts for Water Electrolysis - Wohlgemuth, Marcus; Weber, Moritz L.; Heymann, Lisa; Baeumer, Christoph; Gunkel, Felix (Frontiers in Chemistry, 2022)
The oxygen evolution reaction (OER) is one of the key kinetically limiting half reactions in electrochemical energy conversion. Previous work identified an inverse relationship between activity and the stability of noble metal and oxide OER catalysts in both acidic and alkaline environments: The most active catalysts are chemically unstable under reaction conditions leading to fast catalyst dissolution or amorphization, while the most stable catalysts lack sufficient activity. In this perspective, we discuss the role that epitaxial catalysts play in identifying this activity-stability-dilemma and introduce examples of how they can help overcome it. Our experiments regarding the dependence of both activity and stability on the crystal facet reveal that the inverse relationship is not universal and does not hold for all perovskite oxides in the same manner. In fact, we find that La0.6Sr0.4CoO3-d catalysts follow the inverse relationship, while for LaNiO3-d, the (111) facet is both the most active and the most stable. In addition, we show that both activity and stability can be enhanced simultaneously by moving from La-rich to Ni-rich termination layers. These examples show that the previously observed inverse activity-stability-relationship can be overcome for select materials and through careful control of the atomic arrangement at the solid-liquid interface. This realization re-opens the search for active and stable catalysts for water electrolysis that are made from earth-abundant elements. At the same time, our results showcase that additional stabilization via material design strategies will be required to induce a general departure from inverse stability-activity relationships.